Metatextual Conversations: The Exclusion/Inclusion of Genre Fiction in Public Libraries and Social Media Book Groups. Issue 3 (3rd July 2019) - Veros, Vassiliki
ABSTRACT: Public libraries are institutions with a social inclusion mandate that promote reading and literacies through their collections and programs. Public libraries encourage social inclusion and literary engagement through the provision of book kits for book groups, and apportion cultural legitimacy upon the selections made for these groups of social readers. Using Gerard Genette's schema of transtextualities and through a thematic analysis of NSW public libraries book club kits, reading of literary and 'literary lite' fiction is given a higher status than genre fiction which is predominately excluded from these collections created by librarians who act as gatekeepers and literary authorities. Conversely, book based social media sites such as Goodreads are inclusive of book groups of all genres, from literary to science fiction to romance and many more. The book club selections in these spaces are created by social readers whose engaged digitally captured discussion imparts literary capital through its metatextuality. As the main purpose of book groups is to make commentary upon a selected book, these discussions constitute metatextual conversations. Evidence from the research shows that the physical book group conversations are ephemeral and remain constrained to the physical group, in contrast to the online book group conversation which leaves a perpetual digital document.